Green nursing-home model: The Thammapakon Pho Klang nursing home, Thailand - W. Kulariyasup; J. Horpibulsuk; S. Horpibulsuk (International Association of Lowland Technology, 2018)
This paper presents the design of the new Thammapakon Pho Klang Nursing Home, Nakhon Ratchasima, as a modern model for Thai nursing homes. The nursing home is based on greenbuilding, energy-saving and human-factors engineering principles and covers an area of 102,000 m2 (2,520 acres). The model includes the site design and the buildings of the nursing home, which conforms with green-building and energy-saving principles. The novel nursing home represents a practical approach to the optimization of building use and building resources in the areas of building utilization, water management, waste management, environmentally friendly materials selection, the effect of buildings on the health of building users and the environment, construction, operations, maintenance, and final demolition. The designed buildings include an office building, a hospital, a dormitory for the elderly, a canteen and a multipurpose building. The elderly’s facility design is based on universal design and human-factors engineering. Google’s SketchUp 8 program was used to design the layout of the buildings, the style and size of the openings around the buildings, the building envelope materials, and the position and types of vegetation around the building according to sun direction. It was determined that the overall thermal transmission values (OTTV) and the roof thermal transmission values (RTTV) of the designed buildings are within the prescribed energy-efficient building standard (OTTV < 30 Watt/m2 and RTTV < 10 Watt/m2)